Are the losers of communism the winners of capitalism? The effects of conformism in the GDR on transition success - Max Deter (Deutsches Institut für Wirtschaftsforschung (DIW), 2020)
Following the fall of the Iron Curtain it was important for the acceptance of the new economic and political system that the former Communist elites did not maintain their privileges, and that protesters, who helped to overturn the old system, improved their situation. With newly available panel data on East Germany's socialist past, the German Democratic Republic, we analyze how former Communist elites, dissidents, and the "silent majority" were affected by the transition from socialism into today's market-based democracy. Applying random effects models, the results reveal that the transition reduced economic outcomes for former Communist elites in terms of life satisfaction, income, and employment. The transition had a positive impact on political dissidents and victims of repression. The transition success of the "silent majority" depended on the inner support of the system, that is, low support of the GDR predicts better outcomes in capitalism. Individual preferences for economic liberalism, risk, and trust in others can partly explain selection into Communist elites and dissidents, as well as differences in outcomes of the change from socialism to capitalism for these two groups.
Keywords: H10; N44; P20; D31; 330; East Germany; communist elites; political resistance; autocracy; labor market; life satisfaction